2001
DOI: 10.1603/0022-0493-94.3.658
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Mating Disruption of <I>Sparganothis sulfureana</I> (Lepidoptera: Tortricidae) in Cranberries

Abstract: The feasibility of disrupting mating of Sparganothis fruitworm with a sprayable microencapsulated formulation of (E)-11-tetradecenyl acetate (E11-14:Ac), the major pheromone component, was evaluated in New Jersey during 1996 and 1997 seasons. In both years, application of encapsulated E11-14:Ac, at 25-187.5 g (AI)/ha, reduced the incidence of mating of virgin females placed in treated plots relative to those placed in control plots. Pheromone trap catches were lower in pheromone treated plots, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Polavarapu et al (2001) determined changes in the air and foliage titers of microencapsulated formulation of (E)-11-tetradecenyl acetate after an application in cranberries. In this study, residuals of (E)-11-tetradecenyl acetate in air and foliage samples sharply de- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polavarapu et al (2001) determined changes in the air and foliage titers of microencapsulated formulation of (E)-11-tetradecenyl acetate after an application in cranberries. In this study, residuals of (E)-11-tetradecenyl acetate in air and foliage samples sharply de- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experiments conducted by Facundo (1997) have indicated that application of the major component of the oriental beetle sex pheromone resulted in 64 Ð90% reduction in trap catches in cages treated with the pheromone compared with catches in untreated cages. The recent development of sprayable microencapsulated formulations (3M Canada Company, London, Ontario) will facilitate permeation of oriental beetle pheromone near the soil surface and further improve opportunities for commercialization of mating disruption technology (Polavarapu et al 2001).…”
mentioning
confidence: 99%
“…However, solid-matrix dispensers (such as retrievable lures) of ketone pheromones and other pheromones that would not be tolerance-exempt in broadcast formulations are exempt from tolerance (U.S. EPA 1994), along with any inerts (U.S. EPA 1993). This consideration, along with the small acreages involved, prompted us to not consider broadcast pheromone formulations for mating disruption, a method that has been successful for two tortricid pests in cranberries (Fitzpatrick et al 1995, Polavarapu et al 2001. Recently, another scarab cranberry pest, the Oriental beetle [Exomala orientalis (Waterhouse)], has been disrupted experimentally in blueberry and ornamental nurseries with a microencapsulated mixture of enantiomers of (Z,E)7-tetradecen-2-one (Polavarapu et al 2002).…”
Section: Hoplia Equinamentioning
confidence: 99%
“…Sex pheromone-loaded microcapsules have been used to effectively manage lepidopteran pests of horticultural crops with either frequent application of low rates (Polavarapu et al 2001) or less frequent applications of high rates of sex pheromone (Trimble et al 2003). Determining which strategy is most effective will likely depend on the behavior of the pest, the emission characteristics of the microcapsule, and the deposition and retention of microcapsules within the canopy of the crop.…”
Section: Eventmentioning
confidence: 99%